2014
DOI: 10.1002/dmrr.2598
|View full text |Cite
|
Sign up to set email alerts
|

Low‐grade albuminuria associated with brachial‐ankle pulse wave velocity in young adults with type 2 diabetes mellitus in China

Abstract: Patients with type 2 diabetes with urinary albumin excretion in the upper normal range were still at risk for target organ damage. Low-grade albuminuria might be an early marker for the detection of arterial stiffness in patients with type 2 diabetes, especially in younger patients with type 2 diabetes with shorter durations of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…In terms of arterial stiffness, previous studies reported positive associations of low-grade albuminuria with baPWV and carotid-femoral PWV in normoalbuminuric patients with T2DM [11,12]. In the present study, the strength of the association between ACR and baPWV was attenuated after adjustment for SBP and DBP both in multivariate logistic and regression models, suggesting that the effect was largely mediated by hemodynamic mechanisms.…”
Section: Comparison With Previous Reportsmentioning
confidence: 39%
See 1 more Smart Citation
“…In terms of arterial stiffness, previous studies reported positive associations of low-grade albuminuria with baPWV and carotid-femoral PWV in normoalbuminuric patients with T2DM [11,12]. In the present study, the strength of the association between ACR and baPWV was attenuated after adjustment for SBP and DBP both in multivariate logistic and regression models, suggesting that the effect was largely mediated by hemodynamic mechanisms.…”
Section: Comparison With Previous Reportsmentioning
confidence: 39%
“…Population-based studies showed that mortality rate increases with increasing urine albumin-to-creatinine ratio (ACR), and this relation starts before ACR reaches the levels considered as microalbuminuria [5]. Several studies found a significant association between high normal albuminuria and increased carotid intima-media thickness (IMT) [6e10] and arterial stiffness [11,12], both of which are surrogate markers of changes in vascular morphology and function. These findings highlight the possibility that lowgrade albuminuria may play a role in the pathogenesis of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study in humans shows the association between albuminuria and arterial stiffness determined by pulse wave velocity in non‐hypertensive and non‐diabetic conditions (Kim et al ., ). Similarly, albuminuria has also been related to arterial stiffness in several studies performed in patients with hypertension (Mule et al ., ; Munakata et al ., ) or with type 2 diabetes (Yokoyama et al ., ; Smith et al ., ; Bouchi et al ., ; Huang et al ., ; Sjoblom et al ., ). Consequently, albuminuria has been suggested as an early marker for the detection of arterial stiffness in those patients (Huang et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, albuminuria has also been related to arterial stiffness in several studies performed in patients with hypertension (Mule et al ., ; Munakata et al ., ) or with type 2 diabetes (Yokoyama et al ., ; Smith et al ., ; Bouchi et al ., ; Huang et al ., ; Sjoblom et al ., ). Consequently, albuminuria has been suggested as an early marker for the detection of arterial stiffness in those patients (Huang et al ., ). In accordance with these findings, MRA from MWF rats exhibited reduced increased distensibility, wall stress and strain and, consequently, an increased arterial stiffness determined by the β‐value of the stress–strain relationship.…”
Section: Discussionmentioning
confidence: 98%
“…More recent information in patients with type 2 diabetes mellitus showed that levels of urinary albumin excretion, but not reduced estimated GFR, were associated with increased AS and atherosclerosis [11] . High normal albuminuria in the range (0-30 mg/g) is also associated with aortic stiffness [12] even in younger type 2 diabetic patients with shorter durations of disease [13] , while in newly diagnosed patients with type 2 diabetes mellitus, moderately increased albuminuria was independently associated with AS and vascular inflammation [14] . However, limited data are available whether severely increased albuminuria is associated with AS in nondiabetic hypertensive patients already treated with renin angiotensin aldosterone blockade agents (RAAS) [15] .…”
Section: Introductionmentioning
confidence: 99%